Analysis of the Effect of Work Motivation and Work Environment on Employee Performance at Andi Djemma Masamba Regional Public Hospital - Adela Ainiyyah Calista Rahmat; Mustamin Mustamin; Abdul Rahman; Jangga Jangga; Asnany Asnany (Jurnal Multidisiplin Sahombu, 2026)
Employee performance is a key factor in improving the quality of hospital services, especially in the Emergency Department (ER) which has a high workload and pressure. This study aims to analyze the influence of work motivation and work environment on the performance of ER employees at Andi Djemma Masamba Regional Hospital, as well as to examine the role of individual factors such as income, length of service, and employment status. The study used an analytical observational method with a quantitative descriptive correlational approach through an explanatory survey. The population and sample were all 50 ER employees at Andi Djemma Masamba Regional Hospital using a total sampling technique. Data were collected using a Likert scale questionnaire and analyzed using validity and reliability tests, univariate and bivariate analysis, and multiple linear regression. The results showed that work motivation had a significant partial effect on employee performance, where the higher the work motivation, the higher the employee performance. The work environment also had a significant partial effect on employee performance, indicating that a conducive work environment can improve performance. Simultaneously, work motivation and work environment had a very strong and significant effect on employee performance, with most of the performance variation being explained by these two variables. Furthermore, income factors have a very strong and significant influence on employee performance, while length of service has a significant influence on performance, while employment status has a weak and insignificant influence on employee performance. The conclusion of this study confirms that increasing work motivation and improving the work environment are important strategies for improving the performance of emergency department employees. The results are expected to serve as a basis for the management of Andi Djemma Masamba Regional Hospital in formulating human resource management policies to continuously improve employee performance and the quality of healthcare services.